Electrical and thermal transport properties of natural and synthetic FeAsxS2-x (x ≤ 0.01). (March 2021) - Zuñiga-Puelles, E.; Cardoso-Gil, R.; Bobnar, M.; Veremchuk, I.; Heide, G.; Gumeniuk, R.
Abstract: The combined powder X-ray diffraction, microstructural, local and bulk chemical analyses of natural pyrite single crystals from Reiche Zeche, Johangeorgenstadt and Pretzchendorf (Erzgebirge, Saxony, Germany) showed compositions FeAs0.002(1) S1.998(9), FeAs0.004(1) S1.996(9) and FeAs0.005(1) S1.995(9), respectively. The arsenic doping leads to smaller semiconducting energy gaps ( E g ~0.1–0.2 eV) in comparison with binary FeS2 ( E g  = 0.96 eV), as well as switching of conduction type mechanism from n -to the p -type. These findings are supported by the measurements of the electrical resistivity and Seebeck coefficient of the synthetic FeAs x S2- x series (maximal As-content x  = 0.01 at 773 K). The investigations of sintered FeS2  +  M O2 ( M  = Si, Ti, Zr) composites indicate that some insulating metal oxides as impurities influence less the electrical transport properties of pyrite. All performed studies unambiguously confirmed that p -type conductivity for T  > 300 K is a hallmark of the ternary As-doped FeAs x S2- x ( x  ≥ 0.002) pyrites. Graphical abstract: Image 1 Highlights: Maximal As-content at 773 K in the FeAs x S2- x series is x  = 0.01. The electrical transport mechanism is changing from n -to p -type while doping pyrite (FeS2 ) with arsenic. The arsenic doping leads to the reduction of semiconducting energy gaps from 0.96 eV to ~0.1–0.2 eV. The SiO2, TiO2 and ZrO2 oxide-impurities affect only the electrical and thermal conductivities of the pyrite. Neither As-doping nor oxide-impurities are remarkably reducing the phonon-mediated thermal conductivity of FeS2 .